Thermodynamic Uncertainty Relations in Driven Open Quantum Systems: Bounds on Precision and Dissipation Beyond the Markovian Approximation - Sofia Pereira; Carlos Lopes; Marta Carvalho (Yayasan Adra Karima Hubbi, 2026)
Thermodynamic Uncertainty Relations in Driven Open Quantum Systems: Bounds on Precision and Dissipation Beyond the Markovian Approximation